Look Who’s Talking NOW! Parentese Speech, Social Context, and Language Development Across Time - Ramírez-Esparza, Nairán; García-Sierra, Adrián; Kuhl, Patricia K. (Frontiers in Psychology, 2017)
In previous studies we found that the social interactions infants experience in their everyday lives at 11- and 14-months of age affect language ability at 24 months of age. These studies investigated relationships between the speech style (i.e., parentese speech vs. standard speech) and social context (i.e., one-on-one (1:1) vs. group) of language input in infancy and later speech development (i.e., at 24 months of age), controlling for socioeconomic status (SES). Results showed that the amount of exposure to parentese speech-1:1 in infancy was related to productive vocabulary at 24 months. The general goal of the present study was to investigate changes in (1) the pattern of social interactions between caregivers and their children from infancy to childhood and (2) relationships among speech style, social context, and language learning across time. Our study sample consisted of 30 participants from the previously published infant studies, evaluated at 33 months of age. Social interactions were assessed at home using digital first-person perspective recordings of the auditory environment. We found that caregivers use less parentese speech-1:1, and more standard speech-1:1, as their children get older. Furthermore, we found that the effects of parentese speech-1:1 in infancy on later language development at 24 months persist at 33 months of age. Finally, we found that exposure to standard speech-1:1 in childhood was the only social interaction that related to concurrent word production/use. Mediation analyses showed that standard speech-1:1 in childhood fully mediated the effects of parentese speech-1:1 in infancy on language development in childhood, controlling for SES. This study demonstrates that engaging in one-on-one interactions in infancy and later in life has important implications for language development.